Domestic violence in Toekomsrus township, Randfontein municipality - Kayizzi, Emanuel (My University, 2014)
ABSTRACT Even though most societies proscribe violence against women, the reality is that violations against women’s human rights are often sanctioned under the garb of cultural practices and norms, or through misinterpretations of religious tenets. According to Johnson and Ferraro (2000), domestic violence occurs in every community and across all races and socio-economic groups. It is a very serious problem in need of attention and prevention. Domestic violence happens behind closed doors and is very private, so it becomes difficult to measure or analyse. The measures we do have indicate that it is a global epidemic, primarily affecting women and girls (United Nations Children’s Fund: 1999). Difficulties of analysis are compounded because individuals suffering abuse are vulnerable, so ethical considerations preclude direct interviews. In this study, representatives from ten institutions intervening to reduce domestic violence in the Toekomsrus Township were interviewed about factors and causes of continuing domestic violence in the community. Toekomsrus is part of the Randfontein Municipality. Thirteen major themes were identified through my research as contributors of domestic violence in this community of Toekomsrus. These themes were reduced to four factors: a) Social Factor: Alcoholism, Drug Addiction, Illiteracy, Media. b) Gender Factor: Arrogance, Men’s perception, Provocative behaviour, Religious beliefs. c) Human Factor: Victim occurrence, Social exclusion. d) Economic Factor: Poverty and Unemployment.
Keywords: Family violence -- South Africa